The metabolic modulator trimetazidine triggers autophagy and counteracts stress‐induced atrophy in skeletal muscle myotubes. (12th September 2013) - Ferraro, Elisabetta; Giammarioli, Anna Maria; Caldarola, Sara; Lista, Pasquale; Feraco, Alessandra; Tinari, Antonella; Salvatore, Anna Maria; Malorni, Walter; Berghella, Libera; Rosano, Giuseppe
<x xml:space="preserve">Abstract</x> It has recently been demonstrated that trimetazidine (TMZ), an anti‐ischemic antianginal agent, is also able to improve exercise performance in patients with peripheral arterial disease. TMZ is a metabolic modulator, and the mechanisms underlying its cytoprotective anti‐ischemic activity could be ascribed, at least in cardiomyocytes, to optimization of metabolism. However, regarding the cytoprotection exerted by TMZ on skeletal muscle and allowing the improvement of exercise performance, no information is yet available. In the present study, we investigated in detail the protective effects of this drug on in vitro skeletal muscle models of atrophy. Experiments carried out with murine C2C12 myotubes treated with TMZ revealed that this drug could efficiently counteract the cytopathic effects induced by the proinflammatory cytokine tumor necrosis factor‐α and by the withdrawal of growth factors. Indeed, TMZ significantly counteracted the reduction in myotube size induced by these treatments. TMZ also increased myosin heavy chain expression and induced hypertrophy in C2C12 myotubes, both effects strongly suggesting a role of TMZ in counteracting atrophy in vitro. In particular, we found that TMZ was able to activate the phosphoinositide 3‐kinase–Akt–mammalian target of rapamycin 2 pathway and to reduce the stress‐induced transcriptional upregulation of atrogin‐1, muscle ring finger protein 1, and myostatin, all of which are key molecules involved in muscle wasting. Moreover, this is the first demonstration that TMZ induces autophagy, a key mechanism involved in muscle mass regulation. On the basis of these results, it can be hypothesized that the improvement in exercise performance previously observed in patients could be ascribed to a cytoprotective mechanism exerted by TMZ on skeletal muscle integrity.